2001
DOI: 10.1103/physrevstab.4.122001
|View full text |Cite
|
Sign up to set email alerts
|

Analog analysis ofπ-mode structures: Results and implications

Abstract: The cavities of choice for high-energy synchrotrons and for medium-beta and high-beta accelerating superconducting structures around the world are p-mode structures. A coupled-circuit analysis, allowing for errors in cell frequencies and cell coupling constants, has been used to determine relative on-axis electric field amplitudes between cells, operating frequencies, end-cell tuning, relative on-axis field phase shifts, and field tilts when operated off resonance. Formulas are given for the above information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…The numerical value of L E is chosen in order to reproduce the right field modulation, with the same amplitude in each gap. In agreement with [30], one obtains L E = 2L 1 . On the other hand, a suitable scheme for the coupling cell is a mutual inductance.…”
Section: Example Of a Circuit With A Single Coupling Cellsupporting
confidence: 68%
“…The numerical value of L E is chosen in order to reproduce the right field modulation, with the same amplitude in each gap. In agreement with [30], one obtains L E = 2L 1 . On the other hand, a suitable scheme for the coupling cell is a mutual inductance.…”
Section: Example Of a Circuit With A Single Coupling Cellsupporting
confidence: 68%
“…III C of Ref. [1] showed that dimensional tolerances were a factor of 10 smaller for frequency requirements than for coupling constant requirements. Since frequency tolerances are much more stringent, it is assumed that relative field errors in a cavity are mainly related to frequency errors.…”
Section: A One-step Field Flattening From Frequency Correctionsmentioning
confidence: 99%
“…Terminology and information developed in Ref. [1] are used extensively in the following discussion. Equation development [1] for relative fields in a p-mode cavity made it possible to determine methods for evaluating fields in a cavity with errors and for the actions required to make fields as equal as possible cell-to-cell.…”
Section: One-step Tuningmentioning
confidence: 99%
See 2 more Smart Citations